Pengembangan Sistem Penyemprotan pada Platform Pesawat Tanpa Awak Berbasis Quadcoper untuk Membantu Petani Mengurangi Biaya Pertanian dalam Mendorong Konsep Pertanian Pintar (Smart Farming) - Kris Hariyanto; Djarot Wahju Santoso (Jurnal Nasional Teknologi Terapan (JNTT), 2017)
This study aims to develop the technology of unmanned aircraft for agricultural purposes in realizing the food security of Indonesia. One of the main problems of agriculture in Indonesia is the high cost of agriculture especially the use of chemicals, fertilizer to labor. During this time farmers spend resources such as fertilizer to all plants without the required portion. So it should be attempted an engineering that can reduce the cost of agriculture in terms of labor usage for fertilizing activities and spraying of pests are relatively expensive. The method that will be used for the problem is to make a prototype of pest spraying system by using liquid media on plaform unmanned Aerial Vehicle (UAV) with quadcopter base. Stages in this research include: desk assessment, making of design requirement objective, conceptual making and basic design and making real protoripe UAV. Meanwhile, to know the performance performance of the spraying results is done flight stability test and pest spraying performance . The test results show that with prototype UAV platform using 0.5 Litre liquid media, capable of spraying an area of 2 m2  with a flying time of 10 minutes with a height of 70 cm from the ground. The results of this test will be developed further to be made a larger platform dimensions and capability of transport.